Peningkatan Higiene Sanitasi Dapur Sentral PT XYZ dengan Analisis VRIO (Valuable, Rare, Imitate to Cost, Organized) - Febby Barita Lumban Tobing; Sugiyono Sugiyono; Winiati P. Rahayu (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Cases of food poisoning often originate from households or food service businesses that do not follow proper handling procedures. PT XYZ is a food service business with a central kitchen that supplies 60 outlets. This study aimed to analyze the implementation of hygiene and sanitation practices during operations using the VRIO method, conducted in three research stages. The company demonstrated a commitment to hygiene and sanitation, with observations showing a compliance rate of 80.04%, categorized as good. However, the company had not yet obtained formal certification. A strong correlation (p<0.01) was found between the knowledge level and training of food handlers, as well as the knowledge level of the person in charge of food services, and the implementation of hygiene and sanitation practices. The resource factor showed below-standard performance in the complaint handling system, work environment, and employee capabilities. Similarly, the capability factor demonstrated suboptimal performance in several areas, including raw material storage, the ability to address emerging issues, production efficiency, storage and disposal of goods, supervision and control, and efforts to enhance employee competence in hygiene and sanitation practices.